Interpretasi Kursi dalam Ayat al-Kursi: Komparasi Tafsir Mu’tazilah, Asy’ariyah, dan Maturidiyah - SAPTANADI YUDISTIRA; Edi Komarudin; Ahmad Asep Fathurrohman (Institut Agama Islam Persis Bandung, 2026)
This study aims to examine the interpretation of Kursi in Ayat al-Kursi through a comparative analysis of Muʿtazilah, Asyʿariyah, and Maturidiyah exegesis. The study employs a qualitative approach using a descriptive-analytical and comparative method. This approach is chosen to understand the meaning of the verse by comparing the interpretive tendencies of exegetes belonging to three different theological traditions. The research data are qualitative in nature, not statistical or numerical. The primary sources for this study are al-Kashshaf ʿan Ḥaqaʾiq Ghawamiḍ al-Tanzil wa ʿUyun al-Aqawil fi Wujuh al-Taʾwil, Anwar al-Tanzil wa Asrar al-Taʾwil, and Madarik al-Tanzil wa Ḥaqaʾiq al-Taʾwil. Secondary sources include scholarly references related to the topic, such as articles, books, documents, and others. Data collection was conducted through documentation, while data analysis involved the stages of data inventory, data classification, and data analysis. The three Islamic theological schools Muʿtazilah, Ashʿariyah, and Maturidiyah share the same stance in rejecting anthropomorphic interpretations of the term “kursī” in the Qur’an, although they differ in their degree of acceptance of its literal meaning. The Muʿtazilah interpret “kursī” entirely metaphorically as a symbol of God’s power and knowledge, rejecting any literal meaning in order to safeguard pure monotheism. The Asy’ariyah take a moderate position: they accept taʾwil while also allowing the possibility of a literal meaning without implying resemblance between God and His creation. Meanwhile, the Maturidiyah combine elements of both Muʿtazilah and Asy’ariyah theology, affirming “kursī” as a representation of God’s knowledge and power without implying any physical or material attribute.